The effect of the use of complex molecular profiling in advanced solid organ tumours on clinical decision: Turkey Molecular Profiling in Advanced Cancers Trial (TUMPACT) - Ölmez, Ömer Fatih; Bilici, Ahmet; Er, Özgür; Sevinç, Ali İbrahim; Akman, Tülay; Uslu, Rüçhan; Mandel, Nil Molinas; Yalçın, Şule; Teomete, Mehmet; Görümlü, Gürbüz; Demir, Ahmet Muzafer; Namal, Esat; et al. (Elsevier, 2020)
Background: Molecular genetic profiling (MGP) which has started to take an important part in cancer diagnosis and treatment in recent years, has entered the routineclinical practice much faster than expected. We aimed to evaluate the use of thistechnology in routine practice, the effect of changing the treatment decision.Methods: Two hundred and thirty-four patients who received treatment from 21different centers with OncoDeep MGP platform tests were included, which uses acombination of new generation sequencing (NGS), immunohistochemistry (IHC) andother specific tests (Package Plus).Results: Summary was given in the table. Physician waited for test results in 27%(n¼61) of patients for treatment decision. Prior to MGP analysis patients receivedmedian 2-lines of treatment. The median time between sending the sample abroadfor testing and reaching the result by the physician was 14 days (range:5-71). With thetest results, the physician changed the treatment decision in 51.8% of the patients(n¼118). The most frequent way of drug supply of patients whose treatment decisionwere 64.4% (n ¼ 67) from their own budget. When the treatment responses wereevaluated, the disease control rate was 31.1% and the drug discontinuation wasapplied due to toxicity in 4 patients (3.4%). 63.6% (n ¼ 75) of the patients were foundto be alive with a median follow-up of 18.0 months. (Table).
Keywords: TUMPACT; Organ Tumours; Complex Molecular